2005
DOI: 10.4049/jimmunol.175.7.4789
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Specific CD8+ Lymphocytes in Semen Are Not Associated with Reduced HIV Shedding

Abstract: Sexual contact with HIV-infected semen is a major driving force behind the global HIV pandemic. Little is known regarding the immune correlates of virus shedding in this compartment, although HIV-1-specific CD8+ T cells are present in semen. We collected blood and semen from 27 chronically HIV-infected, therapy-naive men without common sexually transmitted infections or urethral inflammation and measured HIV-1 RNA viral load and cytokine/chemokine levels in both compartments. HIV-1 RNA levels were 10-fold high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 49 publications
1
45
0
Order By: Relevance
“…Although positive correlations between plasma viral loads and genital shedding have been detected previously (2,26,27,36), this association is still somewhat controversial, with some studies failing to find any significant correlation between HIV viral loads in the blood and at the genital mucosa (34,36). Local factors in the genital tract may influence viral replication.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although positive correlations between plasma viral loads and genital shedding have been detected previously (2,26,27,36), this association is still somewhat controversial, with some studies failing to find any significant correlation between HIV viral loads in the blood and at the genital mucosa (34,36). Local factors in the genital tract may influence viral replication.…”
Section: Discussionmentioning
confidence: 90%
“…Cellular and humoral immune responses against HIV have been detected at the cervix and in semen of both HIV exposed and uninfected (highly exposed but persistently seronegative [HEPS]) and HIV-infected individuals (14,15,18,34). It has therefore been suggested that such responses may be important correlates of protection against HIV locally.…”
Section: Magnitude Of Hiv-1 Gag-specific Cd8 T-cell Responses At the mentioning
confidence: 99%
“…It is, therefore, possible that an accumulation of infected CD4 ϩ T cells in semen together with enhanced cellular HIV transcription and replication in activated T lymphocytes (6,17,26,32,65,67,83) could increase the risk of sexual transmission of HIV. Moreover, persistent immune activation of lymphocytes in semen and in blood may impact HIV disease progression and overall clinical outcome.…”
Section: Figmentioning
confidence: 99%
“…17,21 Median levels of blood and seminal plasma cytokines were compared between men with and without atypically high ratios of seminal versus blood plasma HIV-1 RNA levels using the Wilcoxon test. Finally, a separate subanalysis was performed to compare seminal:blood plasma cytokine ratios in men with detectable seminal plasma HIV-1 RNA levels (defined as > 100 copies/ml) and those with undetectable levels ( £ 100 copies/ml), also using the Wilcoxon test.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Berlier et al described a positive correlation with interleukin (IL)-1b, 15 while Storey et al described a positive correlation with RANTES, 16 and Sheth et al showed positive correlations with IL-6, IL-8, IL-12, and interferon (IFN)-c. 17 Furthermore, Lisco et al recently suggested that HIV-1 infection causes a ''reprogrammed cytokine network'' in the seminal plasma with elevated levels of several proinflammatory cytokines including IL-1a, IL-1b, IL-6, and IL-8, which do not correlate with blood plasma cytokine levels. 18 This suggests that cytokine expression is compartmentalized and that seminal plasma cytokines are likely produced within the male genital tract.…”
Section: Introductionmentioning
confidence: 99%